The role of bioenergy for global deep decarbonization: CO2 removal or low‐carbon energy?. Issue 3 (30th January 2020) - Butnar, Isabela; Broad, Oliver; Solano Rodriguez, Baltazar; Dodds, Paul E.
Abstract: Bioenergy is expected to have a prominent role in limiting global greenhouse emissions to meet the climate change target of the Paris Agreement. Many studies identify negative emissions from bioenergy generation with carbon capture and storage (BECCS) as its key contribution, but assume that no other CO2 removal technologies are available. We use a global integrated assessment model, TIAM‐UCL, to investigate the role of bioenergy within the global energy system when direct air capture and afforestation are available as cost‐competitive alternatives to BECCS. We find that the presence of other CO2 removal technologies does not reduce the pressure on biomass resources but changes the use of bioenergy for climate mitigation. While we confirm that when available BECCS offers cheaper decarbonization pathways, we also find that its use delays the phase‐out of unabated fossil fuels in industry and transport. Furthermore, it displaces renewable electricity generation, potentially increasing the likelihood of missing the Paris Agreement target. We found that the most cost‐effective solution is to invest in a basket of CO2 removal technologies. However, if these technologies rely on CCS, then urgent action is required to ramp up the necessary infrastructure. We conclude that a sustainable biomass supply is critical for decarbonizing the global energy system. Since only a few world regions carry the burden of producing the biomass resource and store CO2 in geological storage, adequate international collaboration, policies and standards will be needed to realize this resource while avoiding undesired land‐use change. Abstract : National strategies highlighted in the Paris Agreement rely on bio‐electricity and bio‐heat without using bioenergy generation with carbon capture and storage (BECCS). Conversely, scientific evidence from Integrated Assessment Models suggests a critical role of BECCS in deep decarbonisation scenarios. Usually these models do not consider alternative carbon dioxide removal (CDR) options. Bridging this gap, we assess the role of biomass in global energy systems that also include CDR such as afforestation and direct air capture. We assess scenarios that look for maximum CO2 emissions reduction by 2100, while also accounting for actual biomass supply, CO2 storage availability, and policy developments.